2012
DOI: 10.1002/anie.201205152
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Polymerization of Isoprene and Other 1,3‐Dienes

Abstract: Ironing rubber: Iminopyridine‐based FeCl2 catalysts catalyze the polymerization of 1,3‐dienes and provide stereoselective access to elastomers such as polyisoprenes, polymyrcenes, and polyfarnesenes. The choice of ligand determines the double‐bond geometry in the polymer repeating unit, which can be varied from trans/cis >99:1 to <1:99 (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 26 publications
(23 reference statements)
6
101
0
Order By: Relevance
“…−58 • C, consistent with a 50:50 ratio of 1,4-and 3,4-segments [4,15]. Farnesene homopolymerization was also explored (Table 1, entries 11 and 12); however, the productivities were even lower than for β-myrcene homopolymerization (0.28-0.34 kg·mol −1 ·h −1 ) and a lower monomer loading was required to recover some poly(Fa) (i.e., [Fa] NMR data recorded for the recovered polymer were consistent with those reported in the literature [6,19], and revealed a poly(Fa) microstructure made of a mixture of 1,4-and 3,4-insertions (Supporting Information, Figures S6 and S7). Note that some of those poly(Fa) materials were found to be hardly or even not at all soluble in most of the common solvents (CH 2 Cl 2 , CHCl 3 , THF, 1,2,4-trichlorobenzene), possibly due to the presence of reticulated materials.…”
Section: Homopolymerization Of Myrcene and Farnesenesupporting
confidence: 76%
See 2 more Smart Citations
“…−58 • C, consistent with a 50:50 ratio of 1,4-and 3,4-segments [4,15]. Farnesene homopolymerization was also explored (Table 1, entries 11 and 12); however, the productivities were even lower than for β-myrcene homopolymerization (0.28-0.34 kg·mol −1 ·h −1 ) and a lower monomer loading was required to recover some poly(Fa) (i.e., [Fa] NMR data recorded for the recovered polymer were consistent with those reported in the literature [6,19], and revealed a poly(Fa) microstructure made of a mixture of 1,4-and 3,4-insertions (Supporting Information, Figures S6 and S7). Note that some of those poly(Fa) materials were found to be hardly or even not at all soluble in most of the common solvents (CH 2 Cl 2 , CHCl 3 , THF, 1,2,4-trichlorobenzene), possibly due to the presence of reticulated materials.…”
Section: Homopolymerization Of Myrcene and Farnesenesupporting
confidence: 76%
“…75:25 mixture of α/β; see Figure S21); however, only the β-isomer was incorporated, as evidenced from the 1 H NMR data (see the Supporting Information, Figure S12), whereas the initial ratio [Fa] 0 /[St] 0 was calculated considering the entire amount of farnesene (i.e., both α-and β-isomers). We assume that the trisubstituted C 3 =C bond in the α-isomer, as compared to the disubstituted C 3 =C one in the β-isomer, most likely accounts for lower reactivity of the α-isomer (selective polymerization of β-farnesene was already reported in the literature; see [6]). In addition, an increase in polymerization temperature logically induced an increase in productivity (6 times higher when going from 60 • C to 120 • C in the case of styrene/β-myrcene copolymerization), but also an increase in the amount of terpene incorporated in the copolymer (from 10.9 to 19.7 mol % and from 2.0 to 3.4 mol % for β-myrcene and β-farnesene, respectively; entries 6 and 7 and entries 13-14, respectively).…”
Section: Copolymerizations Of Styrene With β-Myrcene and Farnesenementioning
confidence: 98%
See 1 more Smart Citation
“…For this purpose, we developed av ery efficient task-specific www.chemeurj.org iron catalyst based on ar ecent report that mentionedt he high activity of as eries of iminopyridine iron complexes for isoprene polymerization. [27] To achieve our goal, we kept the basic configuration of such catalytic systemsa nd introduced an aphtalenyl substituent [28] in the ligand framework that can interact with the iron NPs surface through p interactions (Scheme2).…”
Section: Resultsmentioning
confidence: 99%
“…Ritter also reported that similar iminopyridine iron(II) chloride pre-catalysts could be used for the polymerisation of 1,3-dienes following activation by a combination of a trialkylaluminium species and trityl tetrafluoroborate. [128] Chirik reported that bis(imino)pyridine dinitrogen complexes were also active for both [2+2] cycloaddition [97a, 129] and 1,4-hydrovinylation [129] reactions between ethylene and 1,3-dienes (Scheme 56 A). Reaction of ethylene (223) and 1,3-butadiene (224) gave [2+2] cycloaddition product vinylcyclobutane (251) exclusively, whereas ethylene (223) and isoprene (252) gave the 1,4-hydrovinylation product 5-methylhexa-1,4-diene (253).…”
Section: Hydrovinylationmentioning
confidence: 99%